2014
DOI: 10.1016/j.spen.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Status Epilepticus and Refractory Status Epilepticus Management

Abstract: Status epilepticus (SE) describes persistent or recurring seizures without a return to baseline mental status, and is a common neurologic emergency. SE can occur in the context of epilepsy or may be symptomatic of a wide range of underlying etiologies. The clinician’s aim is to rapidly institute care that simultaneously stabilizes the patient medically, identifies and manages any precipitant conditions, and terminates seizures. Seizure management involves “emergent” treatment with benzodiazepines followed by “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 129 publications
0
26
0
Order By: Relevance
“…Intravenous lorazepam is preferred, although non-intravenous diazepam or midazolam are suitable alternatives (Abend et al, 2014; Rogalski and Rogalski, 2015). These anti-epileptic drugs (AEDs) enhance GABA-mediated neuronal inhibition by acting as GABA A R positive allosteric modulators.…”
Section: Pharmacological Inhibitorsmentioning
confidence: 99%
“…Intravenous lorazepam is preferred, although non-intravenous diazepam or midazolam are suitable alternatives (Abend et al, 2014; Rogalski and Rogalski, 2015). These anti-epileptic drugs (AEDs) enhance GABA-mediated neuronal inhibition by acting as GABA A R positive allosteric modulators.…”
Section: Pharmacological Inhibitorsmentioning
confidence: 99%
“…In these patients, mechanisms for self‐termination of seizures fail. Thus, seizures can usually last for several minutes with the high possibility of recurrence (Abend et al., ; Reddy & Kuruba, ). Refractory status epilepticus (RSE) is considered as continuing seizures failing to respond to first‐ and second‐line anticonvulsant therapies (Al‐Mufti & Claassen, ).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the seizures are so severe that they cannot be suppressed even by third‐line therapy (propofol or phenobarbital) (Wheless & Treiman, ). Unlike phenytoin (Abend et al., ; Misra, Kalita, & Bhoi, ; Tiamkao, Sawanyawisuth, & Chancharoen, ), intravenous sodium valproate (IV VPA) can be used safely against various types of SE especially for patients with cardiorespiratory impairments (Trinka et al., ). This nonsedating drug has high tolerability and does not cause severe hemodynamic instability (Brigo et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Second-line treatment involves anesthetic-induced coma with barbiturates such as pentobarbital (in the US) or thiopental (in Europe). 31 In 1988, Lowenstein et al reported that 14 patients had 100% cessation of seizures with barbiturate-induced burstsuppression EEG pattern. However, nine patients had hypotension and seven of them required vasopressors support.…”
Section: Barbituratesmentioning
confidence: 99%